Democratizing Higher Education in Zambia Through Open Access Data - Owango, Joy; Naylor, Daryl; Zulu, Filipo (My University, 2021)
TCC Africa Webinar What is Ministry of Higher Education's Role in Supporting the Zambia Academic Community Through Provision of Open Access Data ? What steps has the Ministry taken in democratizing higher education through open access (partnerships, access to infrastructure and data) What are the challenges that have arisen and also what opportunities has the Ministry taken advantage of in using open access and open science in democratizing higher education in Zambia What does the future hold for the Zambia academic community with open access?
Keywords: Zambia; Science Policy; Open Access